Communication Patterns in the Formation of Self-Concept in Early Adults Who Experience Fatherless in Medan City - Teria Sefty Ginting; Humaizi; Rahmanita Ginting (International Journal of Scientific Multidisciplinary Research, 2024)
This research aims to analyze communication patterns in the formation of self-concept in early adults who experience fatherlessness, analyze self-disclosure in early adults, and to analyze communication barriers felt by early adults who experience fatherlessness in Medan City. The theories used in this research are Symbolic Interaction Theory, Self-Concept and Self-Disclosure. This study uses a qualitative method. The number of informants in this study was 6 (six) early adults who experienced fatherlessness. The research results show that the absence of a father causes the emergence of dysfunctional communication patterns in the family which affects various aspects of the informants' lives such as communication with the surrounding environment and their self-concept. Communication barriers found in early adult individuals are psychological barriers or psychological noise, which is caused by the loss of the father's role due to death or his absence in the informant's growth and development during childhood. This condition creates a fear of communicating and causes difficulty in expressing feelings